ANALYSIS OF TEACHER COMPETENCE IN INDONESIAN LANGUAGE LEARNING ASSESSMENT AT SMAN 2 KUPANG TIMUR - Seubelan, Sartiny; Munirah; syahruddin (LP2M IAI Al-Khairat Pamekasan, 2025)
This research is motivated by the importance of assessing student learning outcomes, one of which can be done through the use of assessment rubrics. This rubric allows teachers to plan assessments systematically, carry out learning effectively, and evaluate student learning outcomes to meet the criteria for completeness that have been set. The purpose of this study is to analyze the competence of teachers in planning the Indonesian assessment rubric, examine the implementation of Indonesian learning by teachers, and evaluate student learning outcomes based on the assessments carried out. This study uses a qualitative descriptive approach with the research subject, namely Indonesian language teachers at SMA Negeri 2 East Kupang, Kupang Regency. Data collection is carried out through documentation and observation of learning tools and their implementation. The results of the study show that the professional competence of Indonesian teachers in the school is relatively good. Teachers have carried out their duties with full responsibility, starting from the stage of planning the assessment rubric, the implementation of learning, to the analysis of student learning outcomes systematically and in accordance with the principles of assessment in Indonesian learning.